Differential Diagnosis of Patients with Inconclusive Parkinsonian Features Using [(18)F]FP-CIT PET/CT - Park, Eunkyung (Springer Berlin Heidelberg, 2013)
PURPOSE: It is often difficult to differentiate parkinsonism, especially when patients show uncertain parkinsonian features. We investigated the usefulness of dopamine transporter (DAT) imaging for the differential diagnosis of inconclusive parkinsonism using [(18)F]FP-CIT PET. METHODS: Twenty-four patients with inconclusive parkinsonian features at initial clinical evaluation and nine healthy controls were studied. Patients consisted of three subgroups: nine patients whose diagnoses were unclear concerning whether they had idiopathic Parkinson’s disease or drug-induced parkinsonism (‘PD/DIP’), nine patients who fulfilled neither the diagnostic criteria of PD nor of essential tremor (‘PD/ET’), and six patients who were alleged to have either PD or atypical parkinsonian syndrome (‘PD/APS’). Brain PET images were obtained 120 min after injection of 185 MBq [(18)F]FP-CIT. Imaging results were quantified and compared with follow-up clinical diagnoses. RESULTS: Overall, 11 of 24 patients demonstrated abnormally decreased DAT availability on the PET scans, whereas 13 were normal. PET results could diagnose PD/DIP and PD/ET patients as having PD in six patients, DIP in seven, and ET in five; however, the diagnoses of all six PD/APS patients remained inconclusive. Among 15 patients who obtained a final follow-up diagnosis, the image-based diagnosis was congruent with the follow-up diagnosis in 11 patients. Four unsolved cases had normal DAT availability, but clinically progressed to PD during the follow-up period. CONCLUSION: [(18)F]FP-CIT PET imaging is useful in the differential diagnosis of patients with inconclusive parkinsonian features, except in patients who show atypical features or who eventually progress to PD.